Long-term survival of carotid stenting patients with regard to single- or double-vessel carotid artery disease: a propensity score matching analysis - Veselka, Josef; Hajek, Petr; Štěchovský, Cyril; Horváth, Martin; Adlová, Radka; Roland, Robert; Homolová, Ingrid; Hansvenclová, Eva; Zimolová, Petra (Archives of medical science, 2021)
INTRODUCTION: There is lack of long-term data outside of controlled clinical trials in carotid artery stenting (CAS). In this study, we compared the short-term outcome, long-term survival, and rate of re-interventions for restenosis in patients after CAS, related to the extent of carotid atherosclerosis classified as single-vessel (unilateral) or double-vessel (bilateral) carotid artery disease. MATERIAL AND METHODS: We retrospectively evaluated 599 patients with significant carotid artery stenosis, who underwent 763 CAS procedures, and used the propensity score to match 226 pairs (452 patients) in the single- or double-vessel carotid disease. RESULTS: There was no significant difference in the occurrence of in-hospital major adverse events (3.5% vs. 3.1% of patients in the double-vessel carotid group vs. the single-vessel carotid group; p = 1) The mean follow-up was 6.1 ±4.0 years, and a total of 181 (40%) deaths occurred during 2759 patient-years, which translates into 7.8 and 5.3 deaths per 100 patient-years in the double-vessel carotid group and the single-vessel carotid group, respectively (p < 0.01). The survival in the double-vessel carotid group vs. the single-vessel carotid group at 10 years was 46% (95% CI: 38-54%) vs. 55% (95% CI: 47-63%) (p < 0.01). Twenty-four (11%) patients and 6 (3%) patients underwent re-interventions for restenosis in the double-vessel and the single-vessel carotid disease group, respectively (p < 0.01). CONCLUSIONS: Patients with CAS and significant double-vessel carotid artery disease had similar peri-procedural risk, but had a worse long-term survival, and a higher rate of re-interventions for restenosis compared to the single-vessel carotid artery disease patients.
Keywords: survival; stenting; carotid artery disease